2023
DOI: 10.1021/acs.cgd.3c00619
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-Phase-Mediated Encapsulation of Guest Drug Molecules in the Hexagonal Columnar Form Structure of Polyethylene Glycol/γ-Cyclodextrin-Polypseudorotaxane

Abstract: The drug/(PEG/γ-CD-PPRX) complex is a unique multicomponent supramolecular structure where the drug molecules are incorporated in the intermolecular spaces of the polypseudorotaxane (PPRX) prepared from polyethylene glycol (PEG) and γ-cyclodextrin (γ-CD). Herein, we report a sealed-heating preparation method to obtain an unanticipated polymorphic form of the drug/(PEG/γ-CD-PPRX) complex, which is the hexagonal-columnar (HC) form. The encapsulation efficiency of the six guest drugs was evaluated. The crystallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The PEG/γ-CD-PPRX and the three polymorphic forms of the SA/(PEG/γ-CD-PPRX) complex were prepared according to our previous report . The HC form of PEG/γ-CD-PPRX was used as the starting material, and its particle size was controlled at less than 150 μm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PEG/γ-CD-PPRX and the three polymorphic forms of the SA/(PEG/γ-CD-PPRX) complex were prepared according to our previous report . The HC form of PEG/γ-CD-PPRX was used as the starting material, and its particle size was controlled at less than 150 μm.…”
Section: Methodsmentioning
confidence: 99%
“…SA is typically used in topical formulations to treat chronic skin diseases for its keratolytic, anti-inflammatory, and bacteriostatic properties. , A recent study by Murthy and co-workers demonstrated that SA suffers significant weight loss at skin temperature (32 °C) by sublimation due to its high vapor pressure from its crystalline state as well as topical formulations . The physical stability issues related to the high vapor pressure of APIs have been addressed by cocrystal/salt formation or complexation with CDs. Herein, we investigated the sublimation suppression of SA from the three polymorphic forms of the SA/(PEG/γ-CD-PPRX) complex, which were prepared by the previously reported sealed-heating technique. , The sublimation rate of SA was determined by thermogravimetry under isothermal conditions. The molecular dynamics of the complexes were evaluated by variable temperature 13 C cross-polarization (CP), 13 C pulse saturation transfer (PST) with magic-angle spinning (MAS)-based solid-state NMR techniques, 1 H MAS, and 13 C spin–lattice relaxation time ( T 1 ) measurement using 13 C isotopically labeled SA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation